Factors associated with balance impairments amongst stroke survivors in northern Benin: A cross-sectional study - Oyéné Kossi; Mendinatou Agbetou; Sènadé I. Noukpo; Lisa T. Triccas; Daniel-Eude; Elogni R. Amanzonwe; Thierry Adoukonou (AOSIS, 2021)
Background: Balance impairment is the predominant risk factor for falls in stroke survivors. A fear of falling after stroke can contribute to sedentary lifestyles, increased disability and risk of recurrence, leading to poor quality of life. Objective: To determine the frequency and factors associated with balance impairments amongst stroke survivors at the University Hospital of Parakou. Method: This cross-sectional study included adult stroke survivors. Stroke survivors after discharge were enrolled at the University Hospital of Parakou between 01 January 2020 and 30 September 2020. Balance impairments were measured by using the Berg Balance Scale (BBS), the Timed Up and Go (TUG) and the Get Up and Go (GUG) tests. Results: A total of 54 stroke survivors were included, with a mean age of 58.37 ± 12.42 years and a male predominance of 68.52%. The mean BBS score was 36.87 ± 14.34 with a minimum and a maximum of 10 and 56, respectively. Thirteen (24.07%) had balance impairments (BBS score ≤ 20), 34 (62.96%) had a TUG score ≥ 14 s (abnormal), 9 (16.67%) presented a moderate risk of falling and 6 (11.11%) presented high risk of fall with the GUG test. Post-stroke duration (odds ratio [OR] = 0.04; 95% CI: 0.04-0.30; p 0.01), severity of disability (OR = 8.33; 95% CI: 1.03-67.14; p = 0.03) and the number of physiotherapy sessions (OR = 0.18; 95% CI: 0.03-0.93; p = 0.02) were significantly associated with balance impairments. Conclusion: Our results showed that almost one quarter of stroke survivors after discharge at the University Hospital of Parakou had balance impairments. Post-stroke duration, severity of disability and the number of physiotherapy sessions were significantly associated with balance impairments. Clinical implications: [AQ1] Balance should be regularly assessed in people post-stroke. Further studies should document the content of rehabilitation and any rehabilitative efforts to improve balance in people post-stroke in Benin.